Melacak Bentuk Tafsir Tematik dalam Khazanah Tafsir Klasik: Studi Bentuk Tafsir Tematik dalam Kitab Tafsir Al-Tabari dan Ibnu Katsir - Zaky Mumtaz Ali (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
Thematic interpretation as a method of interpretation is a contemporary term that has just emerged in the modern era. However, the forerunner or basic form of this thematic interpretation has existed since the early days of Islam. This study aims to trace the existence of thematic interpretations in classical exegesis literature, more specifically in the book of Tafsir At-Tabari and Ibnu Katsir. In addition, the form of thematic interpretation in the two books is also the purpose of this research. This research was written using a literature study (Library Research) by reading and reviewing the literature that became the object of the research study. In addition, this study also refers to several works of contemporary scholars who discuss the thematic interpretation methodology as a finished product produced in the modern era. From the study conducted, the author found several basic forms of thematic interpretation in the two books of interpretation.